Prototyping and wave tank testing of a floating platform with point absorbers - Kamarlouei, Mojtaba (2018)
The main aim of this paper is to present the experimental results of a concept of a platform, with several point energy absorbers. A floating circular array of point absorbers, in 1-27 scale, was tested in the wave tank. The hydrodynamic behavior of the platform was studied in different configurations. Moreover, the performance of the platform was assessed in different sea states with and without point absorbers attached to the platform.